Proposal of a design pattern for embedding the concept of social forces in human centric simulation models - Siebers, Peer-Olaf; Deng, YuFeng; Thaler, Jonathan; Schnädelbach, Holger; Özcan, Ender (2018)
There exist many papers that explain the social force model and its application for modelling pedestrian dynamics. None of these papers, however, explains how to implement the social force model in order to use it for systems simulation studies. In this paper we propose a design pattern (reusable template) that supports the implementation of the social force model within an artificial lab to run experiments for human centric systems. It allows considering not only people but also static and moveable markups. We demonstrate how to implement the design pattern in two commonly used agent-based modelling packages, Repast Simphony and AnyLogic. For this we use an illustrative example from the Adaptive Architecture domain. Both packages require a slightly different implementation strategy, due to the API constraints they provide. Overall, we found that the design pattern provides very helpful guidance when working on the individual solutions for the different packages.